EXPLORE THE CULTURE AND BEAUTY OF MALANG WITH SAHID MONTANA - Sinatra, Calvin; Isnaini, Fauziah; Alfa, Yeremia; T, Matthew; Husna, Miftahul; Mcmahon, Brian M.; Shammary, Al (AIBPM Publisher, 2018)
Sahid Montana is one of the 3 star hotels located in Malang City. The hotel is very close to downtown Malang and traditional nuances. In order increase the market of the hotel, Sahid Montana trying to enter international market. The he method that used to achieved this purpose is through tourism, esspecially in Malang city, Indonesia. This tourism program also have another purpose. The purpose is to develop existing tourism in the city of Malang. Sahid Montana trying to offer some interesting packages such as the natural state of Malang to attract foreign consumers of this city. To be better known to foreign levels, make Sahid Montana appear marketing with event-level events abroad. Sahid Montana aslo make a cooperation with another party in order to achieved their purpose. The party are travel agency, government, Sahid Montana Group, ect. This cooperation also give benefits for each side. This distribution channel and marketing methods has been choosed by team 12, because have more benefits, and easy to be implemented. The parnership’s benefits of this method are for Sahid Montana, another party, government and tourism industry in Malang city. Beside it, the marketing’s benefits are bigger range of promotion, lowwer cost and high effectivenes and efficiency.